Plant-fungal interactions in hybrid zones: Ectomycorrhizal communities of willows (Salix) in an alpine glacier forefield. (June 2020) - Arraiano-Castilho, R.; Bidartondo, M.I.; Niskanen, T.; Zimmermann, S.; Frey, B.; Brunner, I.; Senn-Irlet, B.; Hörandl, E.; Gramlich, S.; Suz, L.M.
Abstract: Ectomycorrhizal (EcM) fungi are essential for the establishment of woody perennial plants in the European Alps. From continental to local scales, environmental conditions and plant host characteristics can predict EcM community structure and composition. However, it is unclear whether EcM communities of congeneric host species and their hybrids are differentially structured at local scales. We aimed to i) characterize EcM communities of Salix helvetica, Salix purpurea and their hybrids and ii) elucidate the abiotic and biotic factors affecting EcM communities in hybrid zones. We analysed the EcM communities associated with willows in a glacier valley by combining molecular identification of fungi from individual ectomycorrhizas and from soil. We detected diverse EcM fungi forming non-modular and unnested networks, but we did not find significant differences in the overall EcM fungal community richness or composition among parental species and hybrids. Nevertheless, individual fungi differed regarding host preference. Our results demonstrate that in a sub-alpine hybrid zone with heterogeneous geomorphology, host genotype was not a strong predictor of overall EcM fungal community, but it influenced the occurrence of particular fungi.